Validation and evaluation of a tablet-based dietary record app for adults aged 70 and above - Jette Hinrichsen; Vincent Quinten; Rebecca Diekmann (PLoS ONE, 2025)
Objective This study aimed at validating the dietary recording functionality of the NuMob-e-App, developed for adults aged 70 and above, against the 24-hour dietary recall reference standard. Methods 104 independently living adults (mean age 75.8 ± 4.1 years; 58% female) from northwest Germany participated. They recorded their dietary intake on three consecutive days using the App. In parallel, we conducted a structured 24-hour dietary recall via telephone. Nutritional intake was analysed for energy, macronutrients, and food groups defined by the German Nutrition Society. Data were analysed for equivalence using Two One-Sided Tests (TOST), agreement using Intraclass Correlation Coefficients (ICC), and systematic differences using Bland-Altman plots. Results Equivalence could be shown in 20 of the 44 compared variables, ICC variated between 0.677 to 0.951 for the four macronutrients and between 0.714 and 0.968 for the seven food groups. The Bland-Altman plots showed tendency to underestimation by the app in most variables and relatively narrow limits of agreement. Conclusions The NuMob-e-App demonstrated good relative validity for assessing energy, carbohydrate, and protein intake, as well as selected food groups in older adults. While equivalence was not achieved across all 44 variables, agreement was particularly strong for protein and beverages. A general tendency toward intake underestimation by the app was observed. These findings support the app’s potential for use in preventive dietary self-monitoring among seniors.